2019
DOI: 10.3201/eid2509.190581
|View full text |Cite
|
Sign up to set email alerts
|

Bombali Virus in Mops condylurus Bats, Guinea

Abstract: In 2018, a previously unknown Ebola virus, Bombali virus, was discovered in Sierra Leone. We describe detection of Bombali virus in Guinea. We found viral RNA in internal organs of 3 Angolan free-tailed bats ( Mops condylurus ) trapped in the city of N’Zerekore and in a nearby village.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…Since its discovery in 2016, BOMV RNA has been detected in oral and rectal swabs as well as internal organs of Mops condylurus and Chaerephon pumilus bats in Sierra Leone, Kenya and Guinea [20, 41, 42]. These data add to the body of evidence suggesting that bats are a reservoir for filoviruses.…”
Section: Resultsmentioning
confidence: 90%
“…Since its discovery in 2016, BOMV RNA has been detected in oral and rectal swabs as well as internal organs of Mops condylurus and Chaerephon pumilus bats in Sierra Leone, Kenya and Guinea [20, 41, 42]. These data add to the body of evidence suggesting that bats are a reservoir for filoviruses.…”
Section: Resultsmentioning
confidence: 90%
“…Bats are also deeply involved in the ecology of FiVs (5), but their roles to maintain the circulation of FiVs remain largely unknown and therefore need further investigation. In addition, the recent discovery of novel FiVs in bats, especially in different bat species in China (11)(12)(13)(14), has added more mystery to these viruses, and has driven numerous efforts to investigate the background of FiVs in bats (15,16). Such work is critical to prevent the outbreak of, and to control, (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bats have been closely associated with FiVs; e.g., the cave-roosting R. aegyptiacus bats are considered to be natural reservoir hosts for MARV (4-6), cumulative evidence based on serological and virological detections has indicated that various bat species could play a role in the ecological circle of ebolaviruses (5,7,8), and LLOV genome has been detected in M. schreibersii bats in Spain and Hungary (9,10). In addition, a number of novel FiVs have been discovered in bats in China and Africa which are divergent enough to be candidates for new species or even genera (11)(12)(13)(14)(15)(16). Particularly in China, reservoirs (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…It was at the epicentre of the 2013-2016 Ebola outbreak and is considered one of the few African viral "hotspots" at high risk for VHF outbreaks, not only for EVD but also for MVD, LF and CCHF [10]. Recently, the region was the site of discovery of Bombali ebolavirus in bats and Lassa virus in rodents [11,12]. To identify misunderstandings, misconceptions and risk practices in HCW relating to EVD, KAP towards EVD amongst HCW have been assessed in parts of Guinea during the EVD outbreak [13][14][15]: two KAP studies conducted in Guinea's capital concluded a low knowledge, negative attitudes and practices of EVD in HCW [13,14].…”
Section: Introductionmentioning
confidence: 99%